PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN MODEL PICTURE AND PICTURE DI KELAS IV SDN 20 BEROK GUNUNG PANGILUN - Hidayat, Revalina; Suriani, Ari; Habibi; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a Classroom Action Research (CAR) project employing both qualitative and quantitative approaches, conducted over two cycles. Each cycle comprised stages of planning, action implementation, observation, and reflection. The research subjects were the teacher and 25 fourth-grade students at SDN 20 Berok Gunung Pangilun during the January–June semester of the 2025/2026 academic year. Data consisted of observations regarding the teaching module, teacher and student activities during the learning process, and student narrative writing skills resulting from the use of the Picture and Picture model. Data collection techniques included observation, testing, and documentation. The results indicate that the implementation of the Picture and Picture model improved students' narrative writing skills from Cycle I to Cycle II. Regarding lesson planning, the assessment score for the teaching module rose to 95.8%, classified as Very Good (SB). In terms of lesson implementation, teacher activity reached 97.5% (SB), and student activity rose to 97.5% (SB). Learning outcomes also improved: the attitude aspect achieved an average of 97%, the knowledge aspect averaged 90%, and the skills aspect averaged 88.1%, with 23 out of 25 students achieving mastery. Thus, it can be concluded that the *Picture and Picture* model enhances the narrative writing skills of fourth-grade students in the Indonesian Language subject at SDN 20 Berok Gunung Pangilun.